The Reception of Antiquity in the Idiostyle of Oles Gonchar - Кохан, Юрій Іванович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
In the article there are considered such language units as words and collocations connected with the epoch of antiquity from the point of view of their role in forming of Oles Gonchar’s idiostyle. It is noted that the antic epoch enriched both the system of the plot and the characters in the world literature as well as in the Ukrainian one functioning as means of imagery, forming language expression, and performing a style creating function. A notable place in the creative work of the writer is occupied by linguistic means associated with antiquity. The work of Oles Gonchar became an iconic phenomenon in the post-war Ukrainian literature, whose life-giving impulses are pierced by the new XXI century. The creative work of this writer is an important and integral part of Ukrainian literature of the second half of the twentieth century. The defining feature of idiostyle of Oles Gonchar most researchers call the expressive shade of romanticism. The author himself defined his style as poetic realism. The lexicon and phraseology, that are related to the Ancient Greece and Rome, onyms and their derivatives are analysed as markers of O. Gonchar’s style and as components of the language in his fiction. A part of this linguistic material is used by the author in its traditional meaning, performs a nominative function. This phenomenon is mostly seen in the works where the chronotope in one way or another is related to the antiquity. But most antic receptions are means of imagery and function as style creating factors colouring Oles Gonchar’s idiostyle in a lyric, romantic way which is naturally combined with realism.